Character Development through the Mileniial Amil Project: A Learning Experience at SMP Islam Al Azhar 15, Cilacap - Sriyanto, Sriyanto; Rahayu, Sri (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2024)
Social studies education is a subject that can foster student character development and enhance learning outcomes. Social studies education provides students with knowledge and skills in various aspects of social life, including history, geography, economics, and politics. However, in reality, social studies education is still often dominated by lecture and memorization methods, which are less effective in developing students’ character and creativity. Lecture and memorization methods make students passive and less engaged in the learning process. Furthermore, this method does not encourage students to think critically and creatively. The impact of the pandemic on student character has resulted in an increasing level of ignorance and indifference towards others, particularly due to the intensive use of technology, especially cellphones. A creative social studies learning model is a learning model that employs various learning methods and strategies to encourage students to be active, think critically, and creatively. Therefore, a creative project-based social studies learning model is necessary to enhance student character and learning outcomes. Interviews and questionnaires. This millennial Amil project is a collaborative effort involving various parties, including parents and the community that will be the beneficiaries of the activity project. The support of these parties is crucial for the success of this program, particularly the support of the jamiyyah as a representative of parents or guardians of students. In this activity, students will gain valuable insights into Islamic religious education, social studies, civics, English, Indonesian, and ICT. The project aims to cultivate students’ character traits such as caring for others, empathy, and fostering a sense of gratitude. Additionally, it encourages lifelong learning for students.